Amazonissínio: por um sistema jurídico pluridimensional da Amazônia - Bianor Saraiva Nogueira Júnior (2023)
The thesis "Amazonissínio: For a pluridimensional legal system in the Amazon" emerge in the face of the possibility of the biome perishing, proposes the adoption of a legal system that recognizes and integrates the different dimensions of the Amazon, including the cultural, social, environmental and economic diversity of the region. From the meaning of "system" in Greek, the term system means and represents a pluridimensional legal perspective adapted to the specificities of the Amazon. The thesis defends the importance of considering indigenous legal systems and their context, in addition to the Western legal system, to achieve a broader and more sustainable administration of justice in the region. The three-dimensional approach (environment, indigenous peoples and territoriality) is a way of recognizing and integrating the different perspectives and needs present in the Amazon region, in order to achieve a more comprehensive and sustainable justice. The thesis uses the methodology of Legistics suitable for a more inclusive and integrative approach, considering the texts, practices and context of the Amazonian reality beyond the western legal system, in order to protect and promote the diversity, sustainability and well-being of the region.